2017
DOI: 10.1038/s41598-017-13696-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of serum miRNAs as molecular biomarkers for acute Stanford type A aortic dissection diagnosis

Abstract: Early and convenient diagnosis is urgently needed for acute Stanford type A aortic dissection (AAAD) patients due to its high mortality within the first 48 hours. Circulating microRNAs (miRNAs) are promising biomarkers of cardiovascular diseases, however, little is known about circulating miRNAs involved in AAAD. Here, the blood serum was sampled from 104 AAAD+ patients and 103 age-matched donors. Initial screening was conducted using the TaqMan Low Density Array followed by RT-qPCR confirmation. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
0
24
0
1
Order By: Relevance
“…24) Also, miR-26b was discovered to participate in the pathophysiology of many cardiovascular diseases, which can improve myocardial remodeling in myocardial infarction. 25) It is the first time Xu et al 12) found that miR-26b was down-regulated in TAAD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…24) Also, miR-26b was discovered to participate in the pathophysiology of many cardiovascular diseases, which can improve myocardial remodeling in myocardial infarction. 25) It is the first time Xu et al 12) found that miR-26b was down-regulated in TAAD.…”
Section: Discussionmentioning
confidence: 98%
“…11) Moreover, Xu et al displayed that miR-26b was significantly decreased in TAAD and served as a biomarker for TAAD diagnosis, which might provide a new potential therapeutic target for TAAD. 12) Therefore, further understanding the molecular mechanism of miR-26b in the pathogenesis of TAAD is very essential.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, emerging circulating miRNAs have been proven as effective and novel non‐invasive biomarkers for the diagnosis of early AAD. A recent study showed that the serum levels of miR‐25, miR‐29a and miR‐155 are up‐regulated, whereas miR‐26b is down‐regulated in Stanford type A aortic dissection (AAAD) patients compared with controls 204. Moreover, in AD patients tissues, Liao et al demonstrated that miR‐553, miR‐183‐3p, miR‐419‐3p, miR‐338‐5p, miR‐433 and miR‐30c are increased in the aortic tissue of thoracic aortic dissection (TAD) patients, but miR‐24, miR‐93, miR‐768‐5p, miR‐143, miR‐145, miR‐22 and miR‐26b are significantly down‐regulated,205 in which the change of miR‐26b was consistent with the serum levels 204.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…A recent study showed that the serum levels of miR‐25, miR‐29a and miR‐155 are up‐regulated, whereas miR‐26b is down‐regulated in Stanford type A aortic dissection (AAAD) patients compared with controls 204. Moreover, in AD patients tissues, Liao et al demonstrated that miR‐553, miR‐183‐3p, miR‐419‐3p, miR‐338‐5p, miR‐433 and miR‐30c are increased in the aortic tissue of thoracic aortic dissection (TAD) patients, but miR‐24, miR‐93, miR‐768‐5p, miR‐143, miR‐145, miR‐22 and miR‐26b are significantly down‐regulated,205 in which the change of miR‐26b was consistent with the serum levels 204. Functionally, up‐regulated level of miR‐29 can enhance the degradation of extracellular matrix, and reduced level of miR‐143 and miR‐145 can facilitate normal contractile and quiescent VSMCs to synthetic and proliferating phenotype, resulting in medial layer degeneration and aortic aneurysm formation 204, 206.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…Most studies using miRNA as biomarkers have focused on circulating miRNA from plasma [15], while fewer studies have employed miRNA derived from fixed whole blood, which includes miRNA derived from platelets and leukocytes [1618]. In concept, novel miRNA biomarkers may potentially be used to monitor effects of medical therapy on gene expression and posttranslational modifications.…”
Section: Introductionmentioning
confidence: 99%